2017
DOI: 10.1093/nar/gkx274
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplex structure of an anti-proliferative DNA sequence

Abstract: AGRO100 (also known as AS1411) is a G-rich oligonucleotide that has long been established as a potent anti-cancer aptamer. However, the structure of AGRO100 remained unresolved, due to the co-existence of multiple different G-quadruplex conformations. We identified a DNA sequence named AT11, derived from AGRO100, which formed a single major G-quadruplex conformation and exhibited a similar anti-proliferative activity as AGRO100. The solution structure of AT11 revealed a four-layer G-quadruplex comprising of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 41 publications
2
79
0
Order By: Relevance
“…Such stems can be stably formed only with the help of additional stabilizing interactions, such as dimerization and linked two-quartet parallel-stranded DNA GQs. 43 Nevertheless, it does not preclude occurrence of parallel-stranded two-quartet stems in transitory ensembles during folding processes. Antiparallel DNA two-quartet stems as well as RNA two-quartet stems are structurally considerably more stable than the parallel DNA two-quartet stems, although even these species likely require additional stabilizing elements to achieve a detectable thermodynamic stability.…”
Section: Resultsmentioning
confidence: 99%
“…Such stems can be stably formed only with the help of additional stabilizing interactions, such as dimerization and linked two-quartet parallel-stranded DNA GQs. 43 Nevertheless, it does not preclude occurrence of parallel-stranded two-quartet stems in transitory ensembles during folding processes. Antiparallel DNA two-quartet stems as well as RNA two-quartet stems are structurally considerably more stable than the parallel DNA two-quartet stems, although even these species likely require additional stabilizing elements to achieve a detectable thermodynamic stability.…”
Section: Resultsmentioning
confidence: 99%
“…Other cases of multiple loop substitutions in both blocks (Table 3) abolished the left-handed G-quadruplex formation ( Figure S15). Thes equence analysis of Z-G4 together with new experimental evidence shows that as horter motif of 12-nt GT(GGT) 3 Gissufficient for the formation of aG-quadruplex with left-handed helicity.Itisalso this short motif that is able to change the helicity of the otherwise right-handed Gquadruplex forming Block1 within the structure of Z-G4.…”
Section: Angewandte Chemiementioning
confidence: 98%
“…[1] G-quadruplexes are involved in essential cellular processes. [2] Studies have shown that G-quadruplex-forming sequences possess anti-cancer [3] and anti-HIV [4] activities.Such peculiar structures have also been used in nanotechnology. [5] Several G-quadruplex folding topologies have been reported that differ according to their relative strand orientations and loop types.…”
mentioning
confidence: 99%
“…An anti‐cancer DNA aptamer containing 17 guanines AGRO100 (also known as AS1411 ) has been shown to adopt multiple G4 conformations . Single G‐to‐T substitutions at various positions of AGRO100 have resulted in the formation of distinct G4 structures . The substitution at position 11 ( AT11 ) generated a four‐layer parallel G4, while another substitution at position 27 ( AT27 ) resulted in a four‐layer parallel left‐handed G4.…”
Section: Figurementioning
confidence: 99%